THE ROLE OF INNOVATION WORK BEHAVIOR IN MEDIATING SOCIAL SUPPORT AND WORK ENGAGEMENT ON SIDEDIWASDA OPERATOR PERFORMANCE - Wicaksono, Prayogi; Arik Susbiyani; Amalina Maryam Zakiyyah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: The implementation of public service innovations is a pivotal step towards enhancing governance effectiveness. This study examines the role of social support, work engagement, and innovative work behavior (IWB) in improving the performance of operators using the SIDEDIWASDA application in Banyuwangi Regency. Despite its potential, challenges in optimizing application utilization indicate performance gaps among operators. This study aims to analyze the direct and indirect effects of social support and work engagement on operator performance, mediated by IWB. Method: Using a quantitative descriptive and verifiable approach, data were collected from 124 respondents through purposive sampling. The analysis utilized the Structural Equation Model (SEM) with WarpPLS. Results: Results indicate that social support and work engagement have significant direct effects on operator performance, with path coefficients of 0.298 and 0.249, respectively (p = 0.001). Both variables also significantly influence IWB (0.394 and 0.384, p = 0.001). Furthermore, IWB significantly enhances performance (0.346, p = 0.001) and mediates the effects of social support (0.136, p = 0.014) and work engagement (0.133, p = 0.016) on performance. Novelty: This study concludes that fostering innovation behaviors through supportive work environments and engaged employees enhances operator performance. It recommends continuous capacity-building programs and collaborative work cultures to maximize application effectiveness and deliver superior public services.